A multi-referential approach to training in its complexity - Ardouin, Thierry (Education Policy Analysis Archives, 2013)
This paper discusses the complexity in the field of adult training by presenting and displaying a constructivist, psychosocial and multi referential posture. If adult training is part of education, it is incorporated into a plurality of areas, approaches, statutes, actors and publics that should be characterized. Training is interacting with the spheres of education, work and society constituting many "social worlds of training". Adult training is subject to certain paradoxes as logical operational training and people development, personal development and the development of the society. Training must take into account these tensions while keeping its humanistic foundations.